Algerian Teachers’ Perceptions of Learning-Oriented Assessment: Challenges and Insights Post-Integrated Content and Language Professional Development Program - Wafia l Tihal (Journal of Science and Knowledge Horizons, 2025)
The integration of innovative assessment practices, such as Learning Oriented Assessment (LOA), into higher education has increasingly become a focal point, capturing the attention of educators worldwide. In Algeria, however, teachers still face challenges in applying LOA, even after taking part in training programs meant to improve their teaching methods. This small-scale exploratory study investigates how Algerian teachers perceive their teaching practices following their participation in the intensive six-month Integrated Content and Language (ICL) professional development course in 2022.It is also an attempt to explore the challenges encountered with the adoption of Learning-Oriented Assessment approach in Higher Education. The study used a qualitative approach and gathered data through a Google Forms questionnaire sent to teachers who took part in the ICL program. The results show that most of them have started using LOA in their teaching and have noticed clear benefits for their students. However, a number of challenges were identified by the participants and were grouped into three major areas: (a) resistance to change due to being reluctant to move from the traditional ways of assessment to LOA; (b) time constraint, since LOA requires much time in planning and giving feedback; and (c) difficulties in designing effective rubrics for assessment. This study calls for further research to be conducted given that the implementation of LOA is still in progress and it is too early to form definitive conclusions at this stage.